The Relationship between Transient Ischemic Dilation (TID) and Severity of Coronary Artery Disease (CAD) in Patients with Chronic Coronary Syndrome (CCS) in Haji Adam Malik Medan, Indonesia - Tamba, Ratna Mariana; Lubis, Hilfan Ade Putra; Mukhtar, Zulfikri; Sitepu, Andika; Habib, Faisal; Andra, Cut Aryfa; Haykal, T. Bob (CoinReads Media Prima, 2023)
Introduction: TID ratio derived from ratio of LV volume in stress and rest phase of MPS. It is said that this phenomenon has been a useful marker of severe CAD, that can be present with atypical angina. This occurs due to global myocardial hypoperfusion caused by severe and extensive CAD. Method: This study was an analytic observational study with a retrospective cohort design in CCS patients who underwent Myocardial Perfusion SPECT at Haji Adam Malik General Hospital from January 2022 to April 2023. All participants underwent MPS with Tc99m sestamibi with pharmacology Adenosine stress test and coronary angiography. The MPS could be performed before or after coronary angiography without any revascularization procedure between the two examination preocedures. An unpaired t-test analysis was performed to find the mean difference in TID values in the mild CAD and moderate-severe CAD groups. Results: The study subjects totaled 93 people with an average age of 55.87±7.44. It was found that the TID value was significantly different between the two groups of mild and moderate-severe CAD based on Syntax score, 0.906±0.13 vs 1.03±0.11 in the mild vs moderate-severe CAD group (p<0.001). Bivariate analysis showed that in this study, the ratio of TID was only associate with LV ESV and LV EDV in stress phase of MPS (p = 0.001). Conclusion: There is a relationship between TID and CAD severity based on Syntax score with higher TID values in patients with moderate-severe CAD compared to patients with mild CAD. TID ratio was only depends on severity od CAD and directly proportional to the volume of LV in the stress phase, suitable to the theory that said TID ratio comes from ratio of LV volume in stress and rest phase of MPS.